PENGARUH BAHASA SANSKERTA DALAM LATAR LAUT KARYA SASTRA KAKAWIN JAWA KUNO - Prawira, Pande Putu Abdi Jaya (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
The sea in Old Javanese literature is not merely depicted as a geographical backdrop, but also as a symbolically charged entity. This study aims to examine the representation of the sea through lexemes used in kakawin , particularly those derived from Sanskrit equivalents. Employing semantic and digital linguistic approaches, the study analyzes the forms and meanings of the diction employed. The findings indicate that the selection of sea-related vocabulary in kakawin can sometimes be arbitrary, serving primarily to fulfill metrical patterns  guru lagu . Lexemes influenced by Sanskrit account for 17 entries (77.27%), while the remaining 5 lexemes (22.72%) are of indigenous Nusantara origin. The semantic mapping of sea-related words in Old Javanese kakawin literature reveals associations with fluidity, waves, salinity, vastness, and jewels/wealth.